PENGARUH PEMILIHAN KONDISI BATAS, LANGKAH RUANG, LANGKAH WAKTU DAN KOEFISIEN DIFUSI PADA MODEL DIFUSI - Haryanto, Budi (APLIKA Jurnal Ilmu Pengetahuan dan Teknologi, 2008)
Diffusion is one of the important processes involved in pollutant transport. In this study, diffusion equation and its performance were investigated through hypothetical thermal diffusion model. Various boundary conditions, time step, space step, and diffusion coefficients were applied in the model, Result of this study shows that diffusion process will last faster at higher diffusion coefficient. Moreover, the use of free radiation boundary condition type causes the variables at the boundary will remain, that is contrary to that of reflective and partly reflective boundary condition. In addition, truncation error can be minimized if D(t/x2)=0,5